ENDOVASCULAR TREATMENT OF TANDEM CAROTID ARTERY STENOSES IN PATIENTS WITH MULTIFOCAL ATHEROSCLEROSIS (Global Conference on Medical and Health Sciences, 2026)
Tandem stenoses of the brachiocephalic arteries represent a complex form of multifocal atherosclerosis and are associated with an increased risk of ischemic stroke. The aim of this study was to evaluate the safety and effectiveness of endovascular treatment of tandem carotid artery stenoses.
Keywords: carotid artery stenosis; tandem lesions; endovascular treatment; carotid artery stenting; multifocal atherosclerosis; cerebral protection devices; ischemic stroke